Development of Tinnitus at a Low Dose of Sertraline: Clinical Course and Proposed Mechanisms. (15th September 2016) - Miller, Christopher W. T.
Abstract : Introduction . Serotonin is involved in filtering of auditory stimuli. Cochlear input is processed through complex interactions between serotonergic, glutamatergic, and GABAergic neurotransmitter systems. Options for treatment of tinnitus include selective serotonin reuptake inhibitors (SSRIs); however in rare instances this symptom may occur as a side effect of this class of medications. Case Presentation . A 50-year-old woman developed bilateral tinnitus after several weeks of being treated with sertraline 50 mg. She had been on a long-standing daily dose of aspirin 325 mg which had been discontinued shortly before starting sertraline. Medical work-up was negative for her symptom. Shortly after discontinuation of the medication, her tinnitus subsided completely. Discussion . Tinnitus is a rare side effect of sertraline and may be related to particular distribution of serotonin receptor subtypes within the auditory system, and serotonergic agents may reinforce or desensitize the activity of different receptors. Also, there may be a priming effect of salicylate agents on the auditory system, predisposing particular patients to be more sensitive to how auditory stimuli are processed.